Interleukin-1 receptor antagonist production in cultured synovial cells from patients with rheumatoid arthritis and osteoarthritis. Issue 4 (April 1995) - Fujikawa, Y; Shingu, M; Torisu, T; Masumi, S
Abstract : OBJECTIVE–To measure the amounts of interleukin-1 receptor antagonist (IL-1ra) protein produced by cultured synovial cells obtained from patients with rheumatoid arthritis (RA) and osteoarthritis (OA). METHODS–Synovial cells obtained from patients with either RA or OA were cultured and the supernatants were measured for IL-1ra by enzyme linked immunosorbent assay. RESULTS–The synovial cells obtained from patients with RA produced significantly smaller amounts of IL-1ra than did those obtained from patients with OA, in a late passage (third to fifth) without stimulation and a first passage both with and without stimulation (p < 0.025, respectively). In addition, when the patients with RA were divided into two groups according to the maximum number of lining cell layers, the amounts of IL-1ra produced by the proliferative type were smaller than those produced by the less proliferative type (p < 0.025). CONCLUSIONS–The above findings suggest that IL-1ra production in RA synovial cells is suppressed, and that reduced IL-1ra protein production is one of the causes which leads to the proliferation of lining cells and persistent joint inflammation.